Navigating regulatory sandbox initiatives for innovation diffusion in fintech lending: A systematic review - Prastowo, Rahardito Dio; Sensuse, Dana Indra; Lusa, Sofian; Putro, Prasetyo Adi Wibowo (Asian Management and Business Review, 2024)
The development of digital technology has succeeded in providing alternative financial services with the FinTech lending industry. This industry allows direct connection between lenders and borrowers through a digital platform. FinTech lending has unique characteristics that provide advantages over traditional financial institution services, such as utilizing soft information for credit risk assessment, providing unsecured loans, and using third-party platforms to secure transactions. Indonesian government continues to update the regulatory framework for the FinTech industry including the implementation of regulatory sandbox. This effort aims to ensure that the development of digital financial innovation is beneficial and safe for society. Various jurisdictions have also implemented similar initiatives to address issues in FinTech lending, allowing companies to test their operations under regulatory supervision. This research conducted a systematic review using the PRISMA 2020 methodology to understand issues related to FinTech lending and the initiatives provided by regulatory sandboxes to address the issues. The study identified 10 issues in the FinTech lending sector using the Technology, Organization, and Environment (TOE) framework and 11 initiatives from implementing regulatory sandboxes using the Diffusion of Innovation (DOI) framework. Finally, this study highlights the potential for further research regarding the issues of algorithmic bias and monopolistic practices, as well as the exploration of how regulatory sandboxes can mitigate these issues.